Pain relief using smart technology an overview of a new patient-controlled analgesia device. - Rudolph, H. (IEEE Transactions on information technology in biomedicine)
A new adaptive patient-controlled analgesia (PCA) system designed to improve PCA through the use of a variable bolus dose and a variable background infusion is outlined here. The handset allows patients to rate their pain on a scale of 1-10. Data derived from the handset signals are used by an expert algorithm to repeatedly adapt the drug dosage of the bolus and the background infusion according to both pain intensity and patient response to previous dosages. A feasibility study of the system consisted of a small number of randomized, double-blind, crossover clinical trials. The new system was alternated with a conventional system every 12 h. When the new system was active, 12 h questionnaire pain scores were significantly lower and a trend toward fewer bolus requests was found in alternating intervals. In addition, when the new system was used to commence trials, the number of bolus requests were significantly lower and there was a trend toward lower handset scores, lower questionnaire pain scores, and lower verbal pain scores over the entire trial period. The new adaptive PCA system was well accepted by both patients and clinical staff. The trials successfully established the feasibility of the new system. Further development is being carried out as a result.